An L‐shaped nanoprobe for scanning electrochemical microscopy–atomic force microscopy. Issue 6 (5th May 2013) - Lee, Eunjoo; Kim, Minseo; Seong, Jungwoo; Shin, Heungjoo; Lim, Geunbae
Abstract We present an L‐shaped nanoprobe for scanning electrochemical microscopy–atomic force microscopy (SECM–AFM) capable of imaging the surface topography and the electrochemical activity of nanostructures of interest. Owing to the geometry of the protrusive peak in the L‐shaped probe, the distance between the probe electrode and the substrate is maintained precisely at ∼100 nm during surface scanning. The reduction in electrode‐to‐substrate distance significantly improves the positive feedback current on top of the electrochemically active nanomaterials. The L‐shaped nanoprobe successfully acquired simultaneous a topographical image and an electrochemical current image of individual carbon nanotubes (CNTs) in a two‐dimensional (2D) CNT network. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Schematic diagram of an L‐shaped nanoprobe for SECM–AFM: the nanoprobe has a triangular frame nanoelectrode and a protrusive insulating peak at the end of the AFM tip. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)